Comparison of Early Maladaptive Schemas and Difficulty in Emotion Regulation Among Adolescent Boys and Girls With and Without Marijuana Use - Moghaddasi, Mahsa; Moraveji, Mahtab (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Objective: Adolescence is a developmental period characterized by significant biological, psychological, and social changes. Consequently, it is associated with increased challenges and negative life events, which heighten adolescents’ distress. This study aimed to compare early maladaptive schemas and difficulty in emotion regulation among adolescent boys and girls with and without marijuana use. Methods and Materials: This applied research employed a causal-comparative design. The study population consisted of all adolescent boys and girls attending counseling centers in District 2 of Tehran in 2022. A total of 100 participants were selected for the study (50 with marijuana use and 50 without marijuana use). The sample of marijuana users was selected using the snowball sampling method. Data were collected using the standardized Young Schema Questionnaire (2005) and the Difficulties in Emotion Regulation Scale by Gratz and Roemer (2004). Data analysis was performed using multivariate analysis of variance (MANOVA) and SPSS.22 software. Findings: The results indicated a significant difference in early maladaptive schemas and difficulty in emotion regulation among adolescent boys and girls with and without marijuana use (P<0.01). Furthermore, there was a significant difference in the mean components of early maladaptive schemas and difficulty in emotion regulation between boys and girls (P<0.01). Conclusion: Given the impact of early maladaptive schemas and difficulty in emotion regulation on the tendency towards addiction among adolescents and young adults, it is possible to increase public awareness about the risk of addiction and develop appropriate skills to cope with these problems.